Report of Gnathophausia ingens (Dohrn, 1870) from bathypelagic region of Bay of Bengal, corroborated by DNA barcoding and 18S rRNA gene sequencing - Balakrishnan, Gunalan; Prasannakumar, C (Indian Journal of Fisheries, 2014)
Gnathophausia ingens is a cosmopolitan bathypelagic large mysid belonging to the family Gnathophausiidae of the order Lophogastrida. Occurrence of this species in Bay of Bengal is reported in this paper. DNA barcodes as well as18S rRNA gene sequences were used to confirm the identity and to delineate the phylogeny of G. ingens. The mitochondrial CO1 sequence shared 97% similarity with G. ingens previously sequenced from deepsea waters of Canada. Phylogram precisely clustered G. ingens isolated from Bay of Bengal with the same species sequenced from Gulf of Mexico proving thesimilarity shared in DNA sequences despite the geographical distance. The sequences produced in this study will act as benchmark for precise identification of G. ingens from Indian waters.